(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2019)
x-ray spectrometric survey shows many radioactive anomalies within the ferruginous siltstone of the lower Um Bogma Formation. The high average eU/eTh values indicate an addition of uranium (migration in) in both the two regions. The results obtained from field measurements show that the indoor annual effective dose in Ramlit Homayier and Heboush area are (48.71 mSv) and (19.70 mSv) respectively while that estimated by HPGE detector were (1.90 and 0.08 mSv). According to AEDE obtained, the dose delivered to each tissue is estimated and it reveals high dose risk to public derived from the exposure to subsurface NORM in Ramlet Homayier more than Heboush area for most body tissues Consequently staying in such levels of NORM requires a high caution and awareness to minimize the health risk accompanied to daily exposure of public and applying radiation protection principals to achieve a better safe working and living environment.